Sentinel lymph node accumulation of Lymphoseek and Tc-99m-sulfur colloid using a “2-day” protocol() - Wallace, Anne M. (2009)
Lymphoseek is a receptor-binding radiopharmaceutical specifically designed for sentinel lymph node (SLN) mapping. We conducted a clinical trial which measured the injection site clearance and sentinel lymph node accumulation after a single intradermal injection of Lymphoseek or unfiltered [(99m)Tc]sulfur colloid (TcSC) using a “2-day” protocol for SLN mapping of breast cancer. Eleven patients with breast cancer participated in this study. Five patients received an intradermal administration of 1.0 nmol of (99m)Tc-labeled Lymphoseek; SLN mapping was performed on four subjects within 19 to 27 h. Six subjects received an intradermal administration of TcSC; SLN mapping was performed on five subjects within 18 to 26 h. Lymphoseek exhibited a significantly (P<.001) faster injection site clearance than TcSC. The mean Lymphoseek clearance half-time was 2.18±1.09 h compared to 57.4±92.8 h for TcSC. The mean sentinel lymph node uptake of Lymphoseek (1.5±1.7%) and TcSC (3.5±3.1%) was statistically equivalent (P=.213). When an intradermal injection is employed, Lymphoseek demonstrated faster injection site clearance than unfiltered [(99m)Tc]sulfur colloid and persistent SLN accumulation for at least 24 h.